ANALYSIS OF CHANGES IN THE SIZE OF UNEMPLOYMENT IN POLAND (Research Bulletins of the Faculty of Economic Sciences, 2021)
The primary goal of this paper is to portraying the sizes of changes of the structure and spatial diversifying of the unemployment in Poland. Temporal dividing lines consti-tute years 1999 -2009, that is current administrative arrangement. The article was made on the basis of unabridged statistical data, and it is presenting meaning of the measure of the GUS publication, especially from series „Register unemployment in Poland ...”.
Keywords: unemployment, register unemployment.